Sertoli-Leydig cell tumor: a propos of a case - Sandoval Díaz, Ither (2014)
The case of a fifty-three years old woman with a Sertoli-Leydig cell tumor stage I is reported; she was treated with surgery alone. A review of the literature on this rare type of tumor is done and recommendations on its treatment is considered.